Securitization as a tool of bank liquidity and funding management before and after the crisis: The case of the EU - Sylwester Kozak; Olga Teplova (e-Finanse: Financial Internet Quarterly, 2012)
Before the financial crisis securitization was commonly considered an efficient way of replacing illiquid assets with liquid securities (ABS), in which the risk was supposed to be adequately compensated by the tranching techniques. However, with the emergence of the crisis investors became more risk aversive and reluctant to incur ABS due to the rapidly deteriorating quality of the underlying assets caused by poor macroeconomic fundamentals. The limited adverse effects of the poor collateral performance is the main reason why chances for recovery of the ABS market in the EU are estimated more highly than in the USA. The analysis indicates that, driven by the ECB repo operations, the securitization market has almost lost the pre-crisis motives behind the issuance of ABS. Banks' attitudes toward securitization as a refinancing tool and a mechanism to extract additional profit underwent a shift. As the findings of the article suggest, after the crisis securitization is widely seen by banks as a liquidity tool within the frame of repo deals with the ECB, and to a lesser extent as a refinancing tool. Market regulation contributed considerably to this shift.
Keywords: F21; F36; G15; G21; 330; Financial system; ECB; Securitization